Intracellular free flavin and its associated enzymes participate in oxygen and iron metabolism in Amphibacillus xylanus lacking a respiratory chain. Issue 6 (9th May 2018) - Kimata, Shinya; Mochizuki, Daichi; Satoh, Junichi; Kitano, Ken; Kanesaki, Yu; Takeda, Kouji; Abe, Akira; Kawasaki, Shinji; Niimura, Youichi
Abstract : Amphibacillus xylanus is a recently identified bacterium which grows well under both aerobic and anaerobic conditions and may prove useful for biomass utilization. Amphibacillus xylanus, despite lacking a respiratory chain, consumes oxygen at a similar rate to Escherichia coli (130–140 μmol oxygen·min −1 ·g −1 dry cells at 37 °C), suggesting that it has an alternative system that uses a large amount of oxygen. Amphibacillus xylanus NADH oxidase (Nox) was previously reported to rapidly reduce molecular oxygen content in the presence of exogenously added free flavin. Here, we established a quantitative method for determining the intracellular concentrations of free flavins in A. xylanus, involving French pressure and ultrafiltration membranes. The intracellular concentrations of flavin adenine dinucleotide (FAD), flavin mononucleotide (FMN), and riboflavin were estimated to be approximately 8, 3, and 1 μm, respectively. In the presence of FAD, the predominant free flavin species, two flavoproteins Nox (which binds FAD) and NAD(P)H oxidoreductase (Npo, which binds FMN), were identified as central free flavin‐associated enzymes in the oxygen metabolic pathway. Under 8 μm free FAD, the catalytic efficiency ( k cat / K m ) of recombinant Nox and Npo for oxygen increased by approximately fivefold and ninefold, respectively. Nox and Npo levels were increased, and intracellular FAD formation was stimulated following exposure of A. xylanus to oxygen. This suggests that these two enzymes and free FAD contribute to effective oxygen detoxification and NAD(P) + regeneration to maintain redox balance during aerobic growth. Furthermore, A. xylanus required iron to grow aerobically. We also discuss the contribution of the free flavin‐associated system to the process of iron utilization. Abstract : Amphibacillus xylanus is known to consume large amounts of oxygen despite lacking a respiratory chain. The free flavin‐associated enzyme system plays a role in the effective NAD(P)H reoxidation system in the energy metabolic pathway, passing reducing equivalents of NAD(P)H to molecular oxygen and ferric iron via the reduced form of free flavin.